120k views
1 vote
What is the simplified expression for the expression below? 4(3x – 2) + 6x(2 – 1) 24x – 3 18x – 8 18x – 7 24x – 14

User Jaumesv
by
4.0k points

2 Answers

1 vote

Answer:

The answer is 18x - 8

Explanation:

User Fossmo
by
4.5k points
0 votes

Answer:

18x-8

Explanation:

Given expression:

=4(3x-2)+6x(2-1)

The expression has to be simplified using the basic rules of mathematics,

In order to simplify the given expression,

We can see that the expression written in second bracket (2-1) which can be solved so,

=4(3x-2)+6x(1)

Multiplying 4 inside the bracket (3x-2)

=12x-(4)(2)+6x

=12x-8+6x

=18x-8 ..

User Ajduke
by
4.6k points